Efficacy of B-type natriuretic peptide is coupled to phosphodiesterase 2A in cardiac sympathetic neurons - Li, D; Lu, C; Hao, G; Wright, H; Woodward, L; Liu, K; Vergari, E; Surdo, N; Herring, N; Zaccolo, M; Paterson, D (American Heart Association, 2015)
Elevated B-type natriuretic peptide (BNP) regulates cGMP-phosphodiesterase activity. Its elevation is regarded as an early compensatory response to cardiac failure where it can facilitate sympathovagal balance and cardiorenal homeostasis. However, recent reports suggest a paradoxical proadrenergic action of BNP. Because phosphodiesterase activity is altered in cardiovascular disease, we tested the hypothesis that BNP might lose its efficacy by minimizing the action of cGMP on downstream pathways coupled to neurotransmission. BNP decreased norepinephrine release from atrial preparations in response to field stimulation and also significantly reduced the heart rate responses to sympathetic nerve stimulation in vitro. Using electrophysiological recording and fluorescence imaging, BNP also reduced the depolarization evoked calcium current and intracellular calcium transient in isolated cardiac sympathetic neurons. Pharmacological manipulations suggested that the reduction in the calcium transient was regulated by a cGMP/protein kinase G pathway. Fluorescence resonance energy transfer measurements for cAMP, and an immunoassay for cGMP, showed that BNP increased cGMP, but not cAMP. In addition, overexpression of phosphodiesterase 2A after adenoviral gene transfer markedly decreased BNP stimulation of cGMP and abrogated the BNP responses to the calcium current, intracellular calcium transient, and neurotransmitter release. These effects were reversed on inhibition of phosphodiesterase 2A. Moreover, phosphodiesterase 2A activity was significantly elevated in stellate neurons from the prohypertensive rat compared with the normotensive control. Our data suggest that abnormally high levels of phosphodiesterase 2A may provide a brake against the inhibitory action of BNP on sympathetic transmission.